2021
DOI: 10.1038/s41560-021-00786-w
|View full text |Cite|
|
Sign up to set email alerts
|

Semi-solid alkali metal electrodes enabling high critical current densities in solid electrolyte batteries

Abstract: The need for higher energy density rechargeable batteries has generated interest in alkali metal electrodes paired with solid electrolytes. However, metal penetration and electrolyte fracture at low current densities have emerged as fundamental barriers. Here, we show that for pure metals in the Li-Na-K system, the critical current densities scale inversely to mechanical deformation resistance. Furthermore, we demonstrate two electrode architectures in which the presence of a liquid phase enables high current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
92
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(94 citation statements)
references
References 48 publications
2
92
0
Order By: Relevance
“…This is in line with findings from Park et al. They showed that pure alkali metals have CCDs that scale inversely to their yield stress [136] . The stress exponent value of sodium suggests that the rate‐controlling mechanism is dislocation climb, which was also proposed for lithium [134] .…”
Section: Negative Electrode Interface Modifications and Dendrite Growthsupporting
confidence: 89%
See 1 more Smart Citation
“…This is in line with findings from Park et al. They showed that pure alkali metals have CCDs that scale inversely to their yield stress [136] . The stress exponent value of sodium suggests that the rate‐controlling mechanism is dislocation climb, which was also proposed for lithium [134] .…”
Section: Negative Electrode Interface Modifications and Dendrite Growthsupporting
confidence: 89%
“…The plastic properties with a yield strength between 0.19 MPa and 0.28 MPa at a strain rate of 10 −3 s −1 may explain the rate capabilities of sodium as the negative electrode [135] . The yield strength is 0.41 MPa, when it is taken as one‐third the hardness for ductile metals [136] . The soft nature of sodium assists in maintaining a uniform deposit morphology and interface contact.…”
Section: Negative Electrode Interface Modifications and Dendrite Growthmentioning
confidence: 99%
“…The use of metallic ≥ alloys in the liquid state, as recently demonstrated for a Li/LLZO system containing a thin liquid Na-K alloy layer, is another promising avenue to achieve both good adhesion and fast Li transport. 42 The strong interaction between alkali metals and metallic substrates is also an important consideration for the selection of current collectors, particularly for alkali metal free designs, in which alkali metal is directly deposited from the SSE onto the current collector (CC). 86 The simple bond breaking model presented in the current study could be further extended to understand the preference for void formation at the Li/SSE versus Li/CC interfaces.…”
Section: Discussionmentioning
confidence: 99%
“…41 Void formation at the Li/LLZO interface was also recently shown to be suppressed by the introduction of a thin liquid Na-K alloy layer. 42 It should also be highlighted that metal vacancy assisted void formation is not unique to all-solid-state batteries and is a common phenomenon observed other fields including radiation induced voids in bimetallic composites 43 and cavity formation during oxide film growth 44,45 .…”
Section: Introductionmentioning
confidence: 99%
“…Significant efforts have been devoted to promoting the critical current density (CCD) during Li deposition/dissolution, that is, the maximum working current density of a SE to avoid metal filament penetration. However, practical application shows that the exploitation of present interface design strategies, such as introducing artificial or sacrificial interlayers, [ 9–11 ] enhancing electrode kinetics, [ 12,13 ] and blocking electron mobility, [ 14 ] are far from satisfactory. There are still large gaps between present CCDs and practical requirements (4 mA cm −2 or even higher).…”
Section: Introductionmentioning
confidence: 99%